Analisis Sistem Informasi Akuntansi Penerimaan Kas dan Pengeluaran Kas pada PT Amaly Mitra Abadi Sulawesi di Kota Makassar - Udianisa, Fitri; Anwar, Samsinar; Azis, Fajriani (Economic Reviews Journal, 2024)
This research aims to determine the application of the cash receipts and cash disbursements accounting information system of PT Amaly Mitra Abadi Sulawesiand to determine the problems in the implementation of the cash receipts and cashdisbursements accounting information system. This type of research is descriptive qualitative research. The type of data used in this research is qualitative data with data collection techniques carried out using documentation and interviews. The results of this research indicate that the implementation of the cash receipts and cash disbursements accounting information system carried out by PT Amaly Mitra Abadi Sulawesi has been implemented effectively. Problems in the implementationof the accounting information system for cash receipts and cash disbursements at PT Amaly Mitra Abadi Sulawesi, there is no clarity regarding the division of tasksbetween the marketing and operational departments.